A Synergistic anti-obesity effects of Phyllanthus urinaria and Adhatoda vasica nees formulation: An investigation in Swiss albino murine model - Pritimoni Das; Manas Das; Pranjan Barman; Naba Kumar Hazarika; Nabajyoti Goswami (Phytomedicine Plus)
Objectives: This work aims at ameliorative evaluation of in vivo and in silico aspects of hydro-ethanolic extract of the Polyherbal Formulation (PHF) of Phyllanthus urinaria L. and Adhatoda vasica nees in High Fat Diet (HFD) induced Swiss albino mice. Methods: Male Swiss albino mice (23–25 g, n = 6) fed with 60 % HFD were treated with a low dose (550 mg/kg b.wt.) and high dose (920 mg/kg b.wt.) of the PHF for 12 weeks. In vivo experiments were performed in subcutaneous adipose tissue and white adipose tissue in HFD induced obese Swiss Albino mice through serum lipid profiling, qPCR analysis of adipogenic, lipolytic genes as well as in silico studies for detection of potent anti-obesity compound through LCMS, molecular docking and simulation based molecular dynamics analysis of target protein CD36. Results: The PHF-treated mice showed significant (p = 0.01) reduction of obesity by improving lipolysis and lowered adipogenesis than the non-treated obese group. The identified compound Granisetron showed higher binding energy as well as standard stability and notably higher interaction towards Granisetron in 100 ns with CD36 receptor than standard drug (∆Gbind value -106.32 ± 2.51). Conclusion: The study validated the efficacy of our novel PHF against HFD-induced obesity in a dose-related manner thereby establishing itself as a potential translational medicine, ensuring the utmost therapeutic value.